Alcohol's contribution to cancer is underestimated for exactly the same reason that its contribution to cardioprotection is overestimated. (27th November 2016) - Stockwell, Tim; Zhao, Jinhui
Abstract : Commentary to:Alcohol consumption as a cause of cancer